GOD-CONCEPT: "SUPREME BEING" IN AFRICAN TRIBAL RELIGIONS - Tovagonze, Venance (Journal of Dharma, 1992)
Many European writers, who made a general survey on African tribal beliefs in the past, have described African Religions in their own ways. Many have maintained that God has no place in African tribal Religions, or that belief in God is due to the influence of hierarchical society. Some have said that God in African tribals is nothing more than a glorified Ancestor, or that belief in God is the reflection of the worship of nature, that Africans are Animists, that magic is the mother of African Religions. Others have said that God is believed in, yet, is thought of as so great that no regular worship is offered to Him.